Breaking Coal Lock-In: Unravelling the Policy Hurdles to Decarbonising Indonesia’s Energy Sector - Kartika, Hansen Sukma; Muhyidin, Ali (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2024)
The Indonesian government has ratified the 2015 Paris Agreement, thereby committing itself to a climate commitment to achieve zero carbon emissions by 2060 and to keep the Earth's temperature rise within 1.5 degrees Celsius above the pre-industrial average. This commitment is being implemented in various ways, including the decarbonisation of the electricity sector. This policy was promulgated in Presidential Regulation 112/2022 regarding acceleration of renewable energy development and Ministry of Finance Regulation 103/2023 on the fiscal support of energy transition. In this case, many aspects such as institutionalisation, visibility, intentionality, risk avoidance, and differences of interest appear to lead to procedural policy outcomes which later determine th decarbonisation rate of Coal-Fired Power Plants (CFPP). This article seeks to examine the procedural aspects of the early coal-fired power plant retirement policy innovation, based on Howlett's (2014) theory of climate policy innovation. This research employs qualitative methods, including in-depth interviews with stakeholders and literature studies. This article explains that the policy formulation in Presidential Regulation 112/2022 tends to be procedurally negative and hampers several CFPPs' early retirement processes in West Java and Banten. The weaknesses of this policy are clearly visible in the form of administrative delays and criteria restrictions. By contextualizing energy policy within the broader framework of public governance in Southeast Asia, the article emphasizes the relevance of inclusive, non-Western approaches to policy reform and public service delivery.